Teknifikasi sebagai Problem Pertanian Modern: Technification as a Modern Agricultural Challenge - Yongki Sutoyo; Moh. Isom Mudin; Aswin Syafril Ferdiansyah; Inas kamila (Indonesian Journal of Islamization Studies, 2023)
The Advancement of Agricultural Technology in Conjunction with the Modernization Wave: Not Only Progress and Convenience, but Also Confrontation with Agricultural Problems The progression of agricultural technology alongside the currents of modernization has yielded not only advancement and increased ease in human existence but has also precipitated a series of agricultural quandaries. From a philosophical vantage, the essence of technology resides in its framework, which perceives nature as an instrument amenable to human engineering. The process of technological development, or technification, within modern agriculture, is fraught with predicaments. Consequently, this exposition seeks to delve into these predicaments concerning the human perspective on both nature and its subsequent contextualization within the Islamic framework. The predicaments associated with technification in agriculture can be delineated into four salient facets. First, there is the concomitant technological worldview that accompanies it. Second, its predominant focus gravitates towards the resolution of "how to" inquiries. Third, it exhibits an orientation geared explicitly towards efficiency and sophistication. Lastly, it contributes to the attenuation of the sensory experiences of humans with regard to the natural world.